2022
DOI: 10.1111/fare.12764
|View full text |Cite
|
Sign up to set email alerts
|

“Euphoria”: Trans children and experiences of prepubertal social transition

Abstract: Objective: This research explored experiences of prepubertal social transition, listening to trans children who were affirmed in childhood, as well as hearing from their parents. Background: Despite being a topic of significant importance, there is limited qualitative literature on parents' or indeed children's experiences of prepubertal social transition and little qualitative research on how childhood rejection or affirmation influences well-being. Method: This study examines qualitative data from 30 parents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 60 publications
3
8
0
Order By: Relevance
“…Due to the recent emergence of the first organizations of families of trans children and adolescents, the real state of the situation became more widely known and visible. These community networks are key for parents, providing them with support by increasing their knowledge, resources, and confidence such that they can support and advocate for their children (Galman, 2020;Horton, 2021;Horton, 2022). However, despite the influence of these family networks, there is still no consensus on how to support trans children, and studies of their experiences have emerged only relatively recently (Chen et al, 2017;Horton, 2022;Olson et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Due to the recent emergence of the first organizations of families of trans children and adolescents, the real state of the situation became more widely known and visible. These community networks are key for parents, providing them with support by increasing their knowledge, resources, and confidence such that they can support and advocate for their children (Galman, 2020;Horton, 2021;Horton, 2022). However, despite the influence of these family networks, there is still no consensus on how to support trans children, and studies of their experiences have emerged only relatively recently (Chen et al, 2017;Horton, 2022;Olson et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, according to recent data, detransitions are quite infrequent: the first longitudinal study on children who have made the transition showed that only 2.5% have retransitioned (Olson et al, 2022). Against this perspective, affirmative approaches emphasize supporting trans children in their identity, without trying to set an age limit or make predictions about their future (Horton, 2022;Temple Newhook et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations